Wartime : Understanding and Behavior in the Second World War. - Fussell, Paul (Oxford University Press, Incorporated, 1989)
Winner of the National Book Award, Paul Fussell's The Great War and Modern Memory was one of the most original and gripping volumes ever written about the First World War. In Wartime, Fussell turns to the Second World War, the conflict he himself fought in, to weave a narrative that is both more intensely personal and more wide-ranging. Fussell examines the immediate impact of the war on common soldiers and civilians; analyzes the euphemisms people needed to deal with unacceptable reality; and, most important, he emphasizes the damage the war did to intellect, discrimination, honesty, individu.